2019
DOI: 10.3390/nu11092110
|View full text |Cite
|
Sign up to set email alerts
|

Water and Beverage Consumption among a Nationally Representative Sample of Children and Adolescents in the United Arab Emirates

Abstract: There are limited studies examining water consumption among individuals in hot climates. We assessed the daily total water intake from plain water, other beverages, and food in a nationally representative sample of children and adolescents aged 6–18 years in the United Arab Emirates. Total water intake was compared against the recommendations of the Institute of Medicine and the European Food Safety Authority. Sociodemographic information, 24 h dietary recall, physical activity levels, and anthropometric data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…Water is one of the main components of the human body, which is vital for the performance of physiological processes, thermoregulation, and transport of nutrients [1,6,7,8]. Water consumption is influenced by numerous factors, including temperature, humidity, as well as the level of physical activity and lifestyle [15,18,21,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water is one of the main components of the human body, which is vital for the performance of physiological processes, thermoregulation, and transport of nutrients [1,6,7,8]. Water consumption is influenced by numerous factors, including temperature, humidity, as well as the level of physical activity and lifestyle [15,18,21,27].…”
Section: Discussionmentioning
confidence: 99%
“…Water is necessary for the development of life and survival [1,8,10,13,24], this is its participation in metabolism, facilitation of cellular metabolism [3,22], modulation of normal osmotic pressure, maintenance of electrolyte balance, regulation of body temperature and many others physiological processes [9,19,23]. It has been proven that both excessive and insufficient water consumption has a negative effect on the health of our body [2,11,14,26,28].…”
Section: Introductionmentioning
confidence: 99%
“…Though the data collected in this study are largely qualitative, the 24-h dietary recall data provided us with a detailed understanding of the type, quantity, and frequency of the foods that individuals were consuming. We Fitness Software, a validated product designed by ESHA Research [34] that has been used in many cross-cultural diet-related research studies [35][36][37]. This nutrient analysis software utilizes multiple verified nutrient databases to allow users to input the type and quantity of food/beverage that participants' consumed and to be able to subsequently view the amount of both macro-and micro-nutrients ingested.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings indicate that the majority of students preferred plastic bottled water (68.02%). A study conducted in the UAE found approximately 80% of the plain drinking water supply for persons aged up to 18 years was through bottled water [36]. Another study conducted in the West Bank found 92% of students drank bottled water on campus [37].…”
Section: Geographical Heterogeneitymentioning
confidence: 99%